2007
DOI: 10.1016/j.pep.2007.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Affinity purification and characterization of a G-protein coupled receptor, Saccharomyces cerevisiae Ste2p

Abstract: We present an example of expression and purification of a biologically active G protein coupled receptor (GPCR) from yeast. An expression vector was constructed to encode the Saccharomyces cerevisiae GPCR α-factor receptor (Ste2p, the STE2 gene product) containing a 9-amino acid sequence of rhodopsin that served as an epitope/affinity tag. In the construct, two glycosylation sites and two cysteine residues were removed to aid future structural and functional studies. The receptor was expressed in yeast cells a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…Similar results are obtained with an antibody generated against the N-terminus of Ste2p. Furthermore, purified Ste2p confirmed by MALDI-TOF and nanospray MS exhibits a 100 kDa at the same position we have attributed to the Ste2p dimer (54). Most importantly, the major conclusion of this paper is that the results indicate that the cytoplasmic ends of TM5 and TM6 undergo conformational change upon ligand binding.…”
Section: Discussionsupporting
confidence: 68%
“…Similar results are obtained with an antibody generated against the N-terminus of Ste2p. Furthermore, purified Ste2p confirmed by MALDI-TOF and nanospray MS exhibits a 100 kDa at the same position we have attributed to the Ste2p dimer (54). Most importantly, the major conclusion of this paper is that the results indicate that the cytoplasmic ends of TM5 and TM6 undergo conformational change upon ligand binding.…”
Section: Discussionsupporting
confidence: 68%
“…Although the Rho-tag has been previously used for isolation of several other recombinant GPCR expressed in mammalian cells [6, 7, 24], yeast [25, 26] and in a cell-free systems [27], the usefulness of this tag for recombinant expression of membrane receptors in E. coli had not been reported yet. We observed that the C-terminal location of the Rho-tag in the fusion construct is obligatory to ensure its accessibility for interaction with specific 1D4 antibody while an appropriate spacer (4 amino acid residues or longer) introduced between the C-terminus of the receptor and the Rho- tag is necessary for high expression levels.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in the expression and purification of membrane proteins have been described for various expression hosts, for example: Escherichia coli (Drew et al 2003(Drew et al , 2005Grisshammer et al 2005), yeast (Wedekind et al 2006;Lee et al 2007), insect cells (Massotte 2003), mammalian cells (Yin et al 2005;Werner et al 2008) and cell-free systems (Klammt et al 2007). However, from approximately 1000 known GPCRs, only five high-resolution 3-D structures of two distinct receptor types have been reported: bovine rhodopsin (Palczewski et al 2000) and opsin (Park et al 2008), squid rhodopsin (Murakami and Kouyama 2008), the human b2-adrenergic receptor Rosenbaum et al 2007) and the turkey b1-adrenergic receptor (Warne et al 2008).…”
Section: Introductionmentioning
confidence: 99%